Psychoanalysis and Black novels : desire and the protocols of race - Tate, Claudia (Race and American culture., 1998)
Although psychoanalytic theory is one of the most potent and influential tools in contemporary literary criticism, to date it has had very little impact on the study of African American literature. Critical methods from the disciplines of history, sociology, and cultural studies have dominated work in the field. Now, in this exciting new book by the author of Domestic Allegories: The Black Heroine's Text at the Turn of the Century, Claudia Tate demonstrates that psychoanalytic paradigms can produce rich and compelling readings of African American textuality. With clear and accessible summaries.